Multispectral, Hyperspectral, and Ultraspectral Remote Sensing Technology, Techniques, and Applications 2006
DOI: 10.1117/12.694283
|View full text |Cite
|
Sign up to set email alerts
|

Surface emissivity effects on thermodynamic retrieval of IR spectral radiance

Abstract: The surface emissivity effect on the thermodynamic parameters (e.g., the surface skin temperature, atmospheric temperature, and moisture) retrieved from satellite infrared (IR) spectral radiance is studied. Simulation analysis demonstrates that surface emissivity plays an important role in retrieval of surface skin temperature and terrestrial boundary layer (TBL) moisture. NAST-I ultraspectral data collected during the CLAMS field campaign are used to retrieve thermodynamic properties of the atmosphere and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Surface emissivity for a given channel is often not updated simultaneously with profiles in the physical iterative process, for example, using emissivities from a regression approach [ Li et al , 2000; Zhou et al , 2006]. Some physical algorithms also retrieve emissivities together with the sounding, but only at selected channels and spectral bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface emissivity for a given channel is often not updated simultaneously with profiles in the physical iterative process, for example, using emissivities from a regression approach [ Li et al , 2000; Zhou et al , 2006]. Some physical algorithms also retrieve emissivities together with the sounding, but only at selected channels and spectral bands.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperspectral emissivity spectrum can be represented in the retrieval process by its EVs derived from laboratory measured hyperspectral emissivity database. Using EVs to represent radiances or parameters to be retrieved has been suggested and attempted by numerous researchers [ Smith and Woolf , 1976; Goldberg et al , 2003; Zhou et al , 2006; Liu et al , 2006].…”
Section: Introductionmentioning
confidence: 99%
“…A relatively large difference in surface skin temperature, shown in Figure 2(k), could be initiated by an error in the land surface emissivity of the retrieval. In a related study, Zhou et al (2006) found that the error in the surface emissivity (or skin temperature) resulted in a large moisture error near the surface, compensating for land surface uncertainty. For example, a large skin temperature difference existing in various points over land (e.g.…”
Section: -8 September Over Potenza Italymentioning
confidence: 99%
“…These parameters are critical in obtaining accurate atmospheric profiles near the surface, especially over land where emissivities have a larger variation 17 . Figure 8 plots surface skin temperature and samples of emissivity images.…”
Section: Retrieval Algorithm and Performance Analysismentioning
confidence: 99%